Comparison of the incidence of intra-operative haemorrhage from ovarian vessels during ovariectomy and ovariohysterectomy of dogs and cats performed by inexperienced surgeons using surgeon's and constrictor knots. Issue 2 (4th March 2022) - Belluzzi, E; Santos, MA; Jifcovici, A; Redolfi, G; Di Virgilio, F; Deneuche, A; Bongartz, AL; Caraty, JA
ABSTRACT: Aims: To compare the incidence of intra-operative haemorrhage from ovarian vessels during ovariectomy (OV) and ovariohysterectomy (OVH) in dogs and cats performed by inexperienced surgeons using surgeon's and constrictor knots to ligate the ovarian pedicles. Methods: All client-owned female dogs (n = 51) and cats (n = 102) that presented for OV or OVH at two referral clinics in Belgium and France from January to June 2019 were included. Surgeries were performed by inexperienced surgeons under the supervision of diplomates or residents of the European College of Veterinary Surgeons. During routine and emergency OV or OVH one pedicle of each animal was ligated using a constrictor knot and the other with a surgeon's knot, the side assigned randomly. Time taken to perform each knot and the number of ligatures that resulted in intraoperative haemorrhage from the ovarian vessels were recorded. Body condition score (BCS) was recorded for 33 dogs and 22 cats. Results: The median time taken to perform constrictor knots in dogs (81 seconds), was longer than for surgeon's knots (69 seconds; p = 0.005). In cats, the median time taken to perform constrictor knots (109 seconds) was also longer than for surgeon's knots (90.5 seconds; p = 0.02). The number of dogs that had intra-operative haemorrhages from pedicles ligated with constrictor knots (2/102; 3.9%) was less than those ligated with surgeon's knots (10/102; 19.6%; p = 0.027). The median BCS of dogs that experienced haemorrhage (n = 8; median 5/9, min 3/9, max 7/9) was higher (p = 0.019) than that of dogs that did not experience haemorrhage (n = 25; median 4/9, min 3/9, max 8/9). There was no evidence (p = 1.0) of a difference in the proportion of cats that experienced intra-operative haemorrhage from pedicles ligated with constrictor knots (3/44; 6.8%) and those ligated with surgeon's knots (2/44; 4.5%). Two-thirds of the haemorrhages with constrictor knots were caused by pedicle rupture during tightening. Conclusions: The rate of intraoperative haemorrhage from the ovarian pedicle was lower when a constrictor knot was used compared to a surgeon's knot in dogs but not in cats. While the constrictor knot was more time consuming to tie this is not likely to have a clinical impact. Use of this knot by inexperienced surgeons in dogs may help to reduce the risk of intraoperative haemorrhage during OVH/OV.